2022
DOI: 10.3390/nano12213902
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of the Photostability Enhancement of Thin-Film Transistors Based on Solution-Processed Oxide Semiconductors Doped with Tetravalent Lanthanides

Abstract: The applications of thin-film transistors (TFTs) based on oxide semiconductors are limited due to instability under negative bias illumination stress (NBIS). Here, we report TFTs based on solution-processed In2O3 semiconductors doped with Pr4+ or Tb4+, which can effectively improve the NBIS stability. The differences between the Pr4+-doped In2O3 (Pr:In2O3) and Tb4+-doped In2O3 (Tb:In2O3) are investigated in detail. The undoped In2O3 TFTs with different annealing temperatures exhibit poor NBIS stability with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…In the bilayer structure, the photo‐induced electrons in the CTL quickly move into the CRL, and then can promote the neutralization of ionized V O with aid of the Pr dopant in the CRL. [ 65 , 66 ] Consequently, the total number of ionized V O in the bilayer decreases, leading to reduced photocurrent of the bilayer TFTs. It may be an average effect.…”
Section: Resultsmentioning
confidence: 99%
“…In the bilayer structure, the photo‐induced electrons in the CTL quickly move into the CRL, and then can promote the neutralization of ionized V O with aid of the Pr dopant in the CRL. [ 65 , 66 ] Consequently, the total number of ionized V O in the bilayer decreases, leading to reduced photocurrent of the bilayer TFTs. It may be an average effect.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the transition of V O states to V O 2+ shallow states induced by illumination would result in the generation of additional delocalized electrons in the CBM. 53 Especially in ambient atmosphere, light exposure would also lead to the oxygen desorption at the back-channel surface of AOS, resulting in the addition of free electrons in the channel. 95 Therefore, negative bias illumination stress (NBIS) reduced the threshold voltage values needed to achieve the same drain current and caused a negative shift in the threshold voltage values (Fig.…”
Section: Stress Induced By Illuminationmentioning
confidence: 99%
“…Furthermore, recently, it has been reported that doping certain metal cations can suppress the activation of V O . 53 Specifically, doping certain metal cations such as tetravalent lanthanides can prevent the activation of V O under illumination stress by converting incoming illumination to non-radiative transition due to charge transfer transition. 54 Thus, choosing an appropriate amount of dopants can result in AOS TFTs with high stability.…”
Section: Introductionmentioning
confidence: 99%